Conflict, complexity and mathematical social science - Burt, Gordon (Emerald, 2010)
Conflict, Complexity and Mathematical Social Science provides a foundational mathematical approach to the modelling of social conflict. The book illustrates how theory and evidence can be mathematically deepened and how investigations grounded in social choice theory can provide the evidence needed to inform social practice. Countering criticism from constructivist viewpoints it shows how discourse is grounded in mathematical logic and mathematical structure. The modelling of social conflict is viewed as an application of mathematical social science and relevant models are drawn from each field of mathematical psychology, mathematical sociology, mathematical political science and mathematical economics. Unique in its multidisciplinary focus the book brings together powerful mathematical conceptualisations of the social world from a wide range of separate areas of inquiry, thereby providing a strong conceptual framework and an integrated account of social situations. It is a vital resource for all researchers in peace science, peace and conflict studies, politics, international relations, mathematical modelling in the social sciences and complexity theory.
Keywords: Social conflict -- Mathematical models.; elektronické knihy; electronic books